Satisfacción del paciente postoperado inmediato sobre el cuidado de enfermería del Servicio de Cirugía del Hospital Regional Docente de Trujillo 2016 - Alva Albarran, Claudia Marcela (2016)
This research is a descriptive cross-sectional; It was performed in order to determine the level of satisfaction of immediate postoperative patients on nursing care in the surgery department of the Regional Hospital of Trujillo 2016. The sample consisted of a total of 200 patients who underwent surgery immediately using a questionnaire type Likert scale CARE-Q divided into five dimensions. The following results which 67.5% was found satisfied with the care received, while the remaining 32.5% are dissatisfied and according to the different characteristics divided into dimensions found in the accessibility dimension 62.5% are satisfied and 37.5% dissatisfied; explains and facilitates in 47.5% were satisfied and dissatisfied 52.5%; in comfort 37.5% are and satisfied 62.5% dissatisfied in it anticipates and 37.5% are satisfied 62.5% dissatisfied, in keeping relationship of trust and 40% are satisfied 60% dissatisfied and dimension monitors and follows up 67.5% were satisfied and 32.5% dissatisfied. We conclude that patients of the surgery are satisfied with postoperative nursing care received.